PENGARUH LOAN TO DEPOSIT RATIO , NON PERFORMING LOAN , DAN PERTUMBUHAN DANA PIHAK KETIGA, TERHADAP PROFITABILITAS PERBANKAN - Sulastiningsih Sulastiningsih; Siti Endarwati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2020)
Profitability is the ability of banks to earn profit through the use of owned assets.The high profitability indicates that good bank performance. This study aims toexamine the effect of Loan to Deposit Ratio (LDR), Non Performing Loan (NPL),and Third Party Fund Growth (DPK) toward profitability measured by Return onAssets (ROA) in Bank Pembangunan Daerah. The study took 25 BankPembangunan Daerah throughout Indonesia in 2013-2017. The data analysistechnique in this research used multilinear regression. The result of the studyshowed that DPK growth has no effect on ROA. LDR has positive significanteffect on ROA. Meanwhile NPL has negative significant effect on ROA.